DAYA SIMPAN SERUNDENG AMPAS KELAPA SEBAGAI PRODUK PENANGGULANGAN ANEMIA GIZI BESI - Amiroh Amiroh; Armita Athennia; Dahlia Nurdini (Media Gizi Pangan, 2023)
Coconut pulp serundeng is a potential product with an iron (Fe) content comparable to vegetable food recommended for people with iron deficiency anemia. This study aims to determine the shelf life of coconut pulp serundeng packed with polyethylene ziplock plastic for two months. Product quality determine by analyze the number of microbes by knowing the Total Plate Number (TPN) and rancidity test by knowing the peroxide value. The results showed that no changes in physical properties were detected for aspects of color, taste, aroma, and texture during storage. The TPN test results showed that the total number of bacteria in each storage period ranges from 101 colonies/gr in accordance with the requirements listed in SNI 01-3715-2000 about dry shredded coconut (desiccated coconut). The results of the rancidity test showed that there was no detected peroxide (Peroxide Value / PV) so it could be concluded that it met the requirements listed in SNI. 3741-2013 on cooking oil. Based on the results of the study, it can be concluded that coconut pulp serundeng can be stored for up to two months using food-grade polyethylene plastic packaging with a ziplock. However, there is still a need for further research to find out, among others, the acceptability of shavings after storage, and the use of another food-grade packaging that is cheaper and more practical and extends the shelf life by more than two months